Compatible Adsorption of Strontium and Zinc Ions as Well as Vitamins on Zeolites - V. Gomonaj; P. Gomonaj; N. Golub; K. Szekeresh; B. Charmas; R. Leboda (Adsorption Science & Technology)
Adsorbents based on natural Sokyrnytsky clinoptilolite have been prepared by treating the base sorbent with aqueous solutions of different salts or acids (HCl, NH 4 OH or NaCl). The separate adsorption of Zr 2+ and Sr 2+ ions and of vitamin B 1 together with the joint adsorption of Sr 2+ ions and vitamin B 1 has been investigated on the prepared samples. The adsorption isotherms of the cations were studied both against concentration and time, when superposition of the adsorption and desorption curves was observed. This suggests the possibility of using such adsorbents for the isolation of heavy metal ions from human organisms without simultaneous loss of vitamin B 1 .